In-cell single-molecule FRET measurement of cytosolic RAF proteins to investigate the structural states and kinetics among them - Okamoto, Kenji; Sako, Yasushi (Frontiers in Molecular Biosciences, 2025)
The structure of a protein is closely linked to its function. Many proteins undergo conformational changes while working in living cells. Consequently, proteins in various structural states coexist in the native cellular environment. Understanding the structural heterogeneity of proteins in living cells is essential for understanding the kinetics of protein reactions. Single-molecule Förster resonance energy transfer (smFRET) is a powerful tool for probing the structure of biomolecules at the single-molecule level. Confocal smFRET measurements, which obtain the smFRET distribution of freely diffusing single molecules, have been successfully applied to cytosolic proteins in living cells. Previous studies on CRAF, a member of the RAF kinase family, revealed the coexistence of at least three conformational states and critical interactions with 14-3-3 proteins. In this study, we applied the method to, in addition to wild-type (WT) CRAF, to mutants at important sites, and to co-expression with other proteins related to RAF activation. The detailed analyses comparing those results suggest the presence of a fourth minor conformational state of CRAF in addition to the previously identified three major states. This fourth state may be related to RAF dimers. Supported by a newly introduced burst intensity analysis, we also found that the three major components can be classified into two groups: two interconvertible components and one independent component. Furthermore, in-cell smFRET measurement of wild-type BRAF, another RAF family member, revealed that its structural distribution consists primarily of a single species, which seemingly corresponds to the lowest FRET component among the three structural states of WT-CRAF. This finding suggests that BRAF has a fundamentally different structural and regulatory mechanism than CRAF.